FORCED MARRIAGES OF CHILDREN AS A FORM OF EXPLOITATION OF HUMAN TRAFFICKING VICTIMS - Božić, Vanda (EU and comparative law issues and challenges series (ECLIC), 2018)
Forced marriages of children are one of the forms of exploitation in the commission of the crime of trafficking in human beings. Children are treated as a commodity, sold to interested parties for the establishment of a family, while the children, victims of trafficking, are completely deprived of their human (children) rights, their health is impaired, they are deprived of the right to education and denied the development of their personality as well as belonging to their own family. Children who have suffered such a serious crime will cope with extremely serious consequences all of their lives. The first part of the paper covers the concept, scope and causes of this form of exploitation of children and the consequences that children need to cope with. The second part presents the international legal framework relating to the suppression of trafficking in children as well as the documents to guarantee international protection of children and their rights. Furthermore, it points out to the national legislation, principally in the field of criminal law, but also other blanket regulations which ensure the protection of children and their rights. This paper also analyses the collected data on child victims of forced marriage. In concluding remarks, listed are recommendations de lege ferenda in combating exploitation of children for the conclusion of forced and arranged marriages and other forms of exploitation of children.